Decrease in Seismic Velocity Observed Prior to the 2018 Eruption of Kīlauea Volcano With Ambient Seismic Noise Interferometry. Issue 7 (8th April 2019) - Olivier, G.; Brenguier, F.; Carey, R.; Okubo, P.; Donaldson, C.
Abstract: The 2018 Kīlauea eruption was a complex event that included deformation and eruption at the summit and along the East Rift Zone. We use ambient seismic noise interferometry to measure time‐lapse changes in seismic velocity of the volcanic edifice prior to the lower East Rift Zone eruption. Our results show that seismic velocities increase in relation to gradual inflation of the edifice between 1 March and 20 April. In the 10 days prior to the 3rd of May eruption onset, a rapid seismic velocity decrease occurs even though the summit is still inflating. We confirm that intereruptive velocity change is correlated with surface deformation, while the velocity decrease prior to eruption is likely due to accumulating damage induced by the pressure exerted by the magma reservoir on the edifice. The accumulating damage and subsequent decrease in bulk edifice strength may have facilitated increased transport of magma from the summit reservoir to the Middle East Rift Zone. Key Points: We use ambient seismic noise interferometry to measure changes in seismic velocity at Kīlauea during to the initiation of the 2018 eruption We detect a rapid seismic velocity decrease 10 days before the eruption This decrease is likely a result of damage accumulation in the edifice due to increased pressure